128k views
4 votes
How do you answer this?

How do you answer this?-example-1

2 Answers

4 votes

Answer:

x = -
(3)/(2)

Explanation:

Using the rules of exponents


(a^m)^(n) =
a^(mn)


a^(-m)
(1)/(a^m)

Note that 16 = 4² and 64 = 4³ , then


16^(x) =
(1)/(64) , can be expressed as


(4^2)^(x) =
(1)/(4^3) , that is


4^(2x) =
4^(-3)

Since the bases on both sides are equal, then equate the exponents

2x = - 3 ( divide both sides by 2 )

x = -
(3)/(2)

User Neossian
by
4.4k points
2 votes

Answer:

x= -3/2

Explanation:

((4)²)^x = 1/(4)³

4²^x = 4³

thus the powers are same then

2x =-3

x=-3/2

User Vansan
by
4.3k points